Сценарний аналіз ринку програмного забезпечення державного сектору України - Гальчинський, Л.Ю.; Луговець, В.В. (Культура народов Причерноморья, 2013)
Проаналізовано сучасний стан ринку програмного забезпечення настільних комп'ютерів і
ноутбуків державного сектора України. Розроблені можливі сценарії розвитку ринку до 2023 року, з
урахуванням стадій життєвого циклу, споживчої цінності і бюджетних обмежень. Запропоновано
методику оцінки сценаріїв, заснованої на використанні методу аналізу ієрархій, методу експертних
оцінок і результатах моделювання життєвих циклів за допомогою моделі дробово-раціонального
тренда з довільною асиметрією. Проанализировано современное состояние рынка программного обеспечения настольных
компьютеров и ноутбуков государственного сектора Украины. Разработаны возможные сценарии
развития рынка до 2023 года, с учетом стадий жизненного цикла, потребительской ценности и
бюджетных ограничений. Предложена методика оценки сценариев, основанная на использовании
метода анализа иерархий, метода экспертных оценок и результатах моделирования жизненных циклов
с помощью модели дробно-рационального тренда с произвольной асимметрией. The current state of the software market of desktop computers and laptops of a public sector of
Ukraine is analyzed. It was established that the majority of operating systems which are used in a public sector
are outdated and modernization demand. In this regard possible scenarios of development are developed for all
operating systems present in the market till 2023, taking into account stages of life cycle, consumer value and
the budgetary restrictions. The model of a fractional and rational trend was applied to the analysis of life cycles
of operating systems with any asymmetry. It was offered to estimate the consumer value of operating systems by
means of method of expert evaluations and within research estimates of consumers and developers were
considered. For an assessment of scenarios the model of the analysis of hierarchies was used. The technique
which allows defining the best scenario depending on the priority direction of public policy in the software
market is as a result offered.